Disordered Wrongdoing, Freedom, and Compassion - Campbell, Benjamin (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Disordered wrongdoing describes behaviour that is causally connected to a wrongdoer’s mental disorder. A common attitude toward such wrongdoing is that the disorder is an “explanation” but not an “excuse” Mental disorders, though, are often thought to be conditions that limit one’s freedom to choose alternative courses of action. These sorts of constraints on freedom are taken in ethical philosophy and democratic judicial systems to strongly reduce one’s moral responsibility for a wrong act, if not remove it altogether in many cases. Rather than focusing on this legal interpretation of responsibility, I will focus on the “holistic” ethical context of how we treat disordered wrongdoers: our ethical comportment. I argue that our basic attitude toward disordered wrongdoers, on account of these constraints in freedom, should be compassionate. I explicitly focus on the meaning of compassion as it relates to a moral obligation to be understanding toward the reasons disordered wrongdoers have for their actions.